(untitled) (Research, Society and Development, 2022)
Leprosy is considered a public health problem, caused by the bacillus Mycobacterium leprae has a predilection for the skin and peripheral nerves and can cause deficiencies and disabilities even after healing. Thus, the study aims to describe the degree of disability of patients affected by leprosy after its cure in Brazil between the years 2019 to 2021. This is a descriptive and quantitative study carried out from secondary data obtained through the Notifiable Diseases Information System - SINAN Net. During the analyzed period, there were a total of 84,449 registered cases of leprosy, where in relation to the clinical type, borderline was the most frequent, there was also a predominance of males, mixed race and age group above 15 years. As for the Degree of Physical Disability, grade zero prevailed, followed by grade 1 and grade 2. Early diagnosis and adequate treatment of the disease and its complications, and the practice of self-care, are the main ways of preventing physical disabilities resulting from leprosy. Thus, it is important to emphasize that the continuity of care provided to the patient should be encouraged, and the patient should be followed up even after healing.